2013
DOI: 10.1016/j.genhosppsych.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s views on depression care in obstetric settings: how do they compare to the views of perinatal health care professionals?

Abstract: Objectives The objectives were to examine patients’ perspectives on patient-, provider- and systems-level barriers and facilitators to addressing perinatal depression in outpatient obstetric settings. We also compare the views of patients and perinatal health care professionals. Method Four 90-min focus groups were conducted with women 3–36 months after delivery (n=27) who experienced symptoms of perinatal depression, anxiety or emotional distress. Focus groups were transcribed, and resulting data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 47 publications
2
86
0
5
Order By: Relevance
“…55,56 Our second finding contributes to the nascent literature on the association of stressors and seeking help for PDS. Examples of barriers to help seeking for depressive symptoms in the literature include perception that primary health care providers lack training and skills in mental health, 9,10,[57][58][59] lack of insight into patient's state-of-mood, 11 stigma, 11,60,61 and lack of services. 62 The prevalence of financial-related stressors, particularly ''partner lost job'' and the association between mothers with financial-related stressors and seeking help for PDS both increased in the 2009-2010 PRAMS compared with 2007-2008 reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…55,56 Our second finding contributes to the nascent literature on the association of stressors and seeking help for PDS. Examples of barriers to help seeking for depressive symptoms in the literature include perception that primary health care providers lack training and skills in mental health, 9,10,[57][58][59] lack of insight into patient's state-of-mood, 11 stigma, 11,60,61 and lack of services. 62 The prevalence of financial-related stressors, particularly ''partner lost job'' and the association between mothers with financial-related stressors and seeking help for PDS both increased in the 2009-2010 PRAMS compared with 2007-2008 reports.…”
Section: Discussionmentioning
confidence: 99%
“…8 Bennett et al found that mothers were more likely to seek help if the topic was broached first by their prenatal caregiver, and black mothers were more likely to seek help compared with white mothers. 9 Inconsistencies in predictors occur across age groups, and reflect variations in geographic region (urban versus rural), education, race/ ethnicity, and parity, as well as family income and relationship status with partner/father of baby. In Massachusetts, health care insurance has been mandatory since 2007, 63 including parity with mental health needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal depression and anxiety are common mental health disorders in pregnancy and the first 12 months post-birth (Howard et al 2014;Byatt et al 2013). Perinatal depression affects between 10 and 17% of women (Austin 2014) and perinatal anxiety between 13 and 20% of women (Austin 2014;Austin et al 2017).…”
mentioning
confidence: 99%
“…In many instances, depression and anxiety disorders coexist (Austin 2014, Austin et al 2017. Perinatal mental health disorders are associated with several adverse outcomes associated with birth, infant development (Byatt et al 2013) and family function (Austin et al 2017). The new Mental Health Care in the Perinatal Period: Australian Clinical Practice Guideline recommend all women receive psychosocial risk assessment and screening for symptoms of depressive and anxiety disorders in early and late pregnancy, and 6-12 weeks post-birth, with repeat assessment as clinically indicated (Austin et al 2017).…”
mentioning
confidence: 99%